Analyzing anemia among quilombola children: An integrative systematic review (Research, Society and Development, 2025)
Objective: To conduct an integrative systematic review on anemia in the Brazilian quilombola child population, its main causes, factors involved, and consequences.  Methodology: The review was guided by the principles established in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The search strategy involved accessing the CAPES Journals Portal and the Virtual Health Library, consulting the following databases: SciELO, Scopus, Web of Science, National Medline/PubMed, and LILACS. Additionally, the Public Health Theses Portal of the VHL and the CAPES Theses and Dissertations Portal were consulted. Results: A total of 36 studies were identified, 10 of which were selected for inclusion in this review. The selected studies were organized into two analytical categories: Socioeconomic Conditions and Limited Access. Conclusion: The review revealed a high prevalence of anemia—particularly iron-deficiency anemia—among children in quilombola communities, reflecting the poor socioeconomic and structural conditions these communities face daily. The findings also showed that limited access to healthcare services, compounded by food insecurity and the lack of effective public policies, perpetuates the cycle of vulnerability and negatively impacts the growth and development of these quilombola children.